Modernization of institutional support for the development of the knowledge economy - Vasina, Alla (Herald of Economics, 2021)
Introduction. The concept of the knowledge economy, which was formed at the end of the twentieth century, clearly outlined the decisive role of the knowledge resources in the ensuring of the sustainable economic growth. However, more than 20 years experience of realization of Ukraine’s efforts to form an effective model of socio-economic development and organically join the European community, using the knowledge potential of the economic transformation, shows the presence of the significant barriers along the way to eliminate the effective mechanisms. It is obvious that the challenges of dynamic technological progress, increasing competition in the world economic space, exacerbation of crises in all spheres of public life highlight the need for a consistent policy of creating a favorable institutional environment for the knowledge component of the national economy.Purpose of the research. The methodological basis of the institutional support for the development of the knowledge economy and identifying approaches to its improvement, taking into account the societal challenges, new risks and threats are substantiated in the scientific study.Research methods. The methodological basis of the study was the use of the systemic and institutional approaches in the process of the theoretical foundations and practice of knowledge economy analyzing. To achieve this objective, the following research methods were used: system analysis, systematization, generalization – in determining the preconditions, factors and results of the knowledge economy; logical – in substantiating the need to modernize the institutional support for the development of the knowledge economy; institutional analysis – in the study of the impact of institutional support on the formation of the knowledge economy.Results. Specific features of the knowledge economy are highlighted. They indicate the need to intensify the processes and develop the mechanisms for its development. The theoretical and methodological basis for the formation of the institutional support for the dynamization of the knowledge economy is substantiated. The trends of the globalized space, which determine the institutional guidelines of the modernization innovation and technological transformations of the national economies are identified. The methodological approaches to the identification of the institutional barriers and untapped opportunities for the development of the knowledge economy as a basis for developing of the conceptual approaches to the modernization of its institutional support are presented. Emphasis is placed on the need for the effective use of the strategic mechanism to provide a clear institutional framework for a consistent active economic policy of knowledge and innovation to improve the development of the national economy. Ways to improve the institutional support for the implementation of mechanisms for the development of the knowledge economy are identified.Perspectives. In the context of the formation of a qualitatively new institutional basis of the knowledge economy development, the issues of establishing of the effective cooperation between the government, educational, scientific, and business institutions towards ensuring of the systemic innovative and technological transformations of the economy is needed; likewise the development and optimal combination of mechanisms of multilevel management of processes of knowledge reset of economy with involvement of stimulating factors at the national, regional, local levels; and the use of the potential of social, value, ethical institutions in the process of formation and use of the knowledge resource of the national economy.